Are there limits to swimming world records? - Nevill, A. M.; Whyte, G. P.; Holder, R. L.; Peyrebrune, M. (International Journal of Sports Medicine, 2007)
The purpose of this article was to investigate whether swimming world records are beginning to plateau and whether the inequality between men and women's swimming performances is narrowing, similar to that observed in running world records. A flattened "S-shaped curve" logistic curve is fitted to 100-m, 200-m, and 400-m front-crawl world-record swimming speeds for men and women from 1 May 1957 to the present time, using the non-linear least-squares regression. The inequality between men and women's world records is also assessed using the ratio, Women's/Men's world record speeds. The results confirm that men and women's front-crawl swimming world-record speeds are plateauing and the ratio between women's and men's world records has remained stable at approximately 0.9. In conclusion, the logistic curves provide evidence that swimming world-record speeds experienced a period of "accelerated" growth/improvements during the 1960 - 1970s, but are now beginning to plateau. The period of acceleration corresponded with numerous advances in science and technology but also coincided with the anecdotal evidence for institutionalised doping. Also noteworthy, however, is the remarkably consistency in the women's/men's world record ratio, circa 0.9, similar to those observed in middle and long distance running performances. These finding supports the notion that a 10 % gender inequality exists for both swimming and running.